Why Cognitive–Cognitive Dual-Task Testing Assessment Should Be Implemented in Studies on Multiple Sclerosis and in Regular Clinical Practice - Beste, Christian; Ziemssen, Tjalf (Frontiers in Neurology, 2020)
Cognitive impairment is prevalent and disabling in multiple sclerosis (MS) and is severely impacting quality of life (QoL). Aside its routine assessment in clinical care, it should more often be implemented as endpoint/outcome measure in clinical trials. However, a fundamental aspect – often neglected in clinical practice and clinical trials – is the assessment of multi-tasking and dual-tasking abilities. In this perspective article, we outline why, given the nature of MS, particularly the assessment of “cognitive-cognitive dual-tasking” is relevant in MS. We delineate how knowledge from basic cognitive science can inform the assessment of this important cognitive impairment in MS. Finally, we outline how the assessment of “cognitive-cognitive dual-tasking” can be implemented in computer-based screening tools (e-health devices) that can not only be used in clinical diagnostics, but also in clinical trials.